Ultimate strengths of triple-ring-stiffened tube-gusset X-joints considering the effect of chord load. (December 2022) - Sitong, Wei; Jinghua, Zhang; Chao, Zhao; Guanghui, Tang; Quangeng, Li; Qing, Sun
Abstract: Triple-ring-stiffened tube-gusset (TRS TG) X-joints are frequently adopted in steel transmission towers to bear the load from braces. It has been generally accepted that the ultimate strengths of the joints are dependent on the chord load. However, it is not yet comprehensively understood how the performance of TRS TG X-joints would be influenced. In this study, finite element models were firstly constructed for typical TRS TG X-joints. The numerical models were validated by the test results of six prototype specimens. Then, they were used for investigation on the effect of chord load on the ultimate strengths of TRS TG X-joints subjected to brace axial compression. Three types of chord loads were considered, including axial load, in-plane bending moment, and a combination of the axial load and the in-plane bending moment. The numerical results indicate that the tensile stresses of the chord are more detrimental than the compressive ones. A moderate compressive axial load on the chord, not exceeding thirty percent of the axial yield capacity thereof, could even enhance the ultimate strength of the joint by 3%. It is also found that the current chord stress functions tend to be too conservative. The ultimate strength of the joint could be underestimated by as much as 40%. Based on an extensive numerical database of TRS TG X-joints, a more accurate chord stress function is proposed, reducing the maximum error to 0.5%.